EFFECT OF DISINFECTANTS BASED ON POTASSIUM PERSULFATE, HYDROGEN PEROXIDE, GLUTARALDEHYDE AND QUATERNARY AMMONIUM COMPOUNDS ON THE GENETIC MATERIAL OF THE PATHOGEN BACTERIA SPECIFIC TO MEAT PROCESSING INDUSTRY - V. N. Afonyushkin; K. A. Tabanyukhov; V. S. Cherepushkina; Yu. S. Khomenko; O. P. Tatarchuk (Теория и практика переработки мяса, 2016)
Abstract The changes in bacterial genetic material under the action of different biocidal products have been investigated. It was confirmed by PCR and genetic engineering that biocidal product Ecocid was able to remove both chromosomal and plasmid DNA, either isolated or contained within the bacterial cells. Using a disinfectant that destroys DNA on the surfaces of meat production equipment is a promising measure to prevent horizontal transfer of unwanted genetic material, such as bacterial genes associated with the resistance to antibiotics, or genes of toxin production.